Protein bioaccessibility from mycoprotein hyphal structure: In vitro investigation of underlying mechanisms. (15th November 2020) - Colosimo, Raffaele; Warren, Frederick J.; Finnigan, Tim J.A.; Wilde, Peter J.
Highlights: Mycoprotein cell walls are highly resilient to mechanical/physical processing and digestion. Intestinal proteases are the main factors controlling protein bioaccessibility from mycoprotein products. Diffusion of proteases through the cell wall is the proposed mechanism which facilitates the high protein bioavailability. An optimal ratio of mycoprotein to enzymes is crucial for protein release. Abstract: Mycoprotein is a food ingredient from filamentous fungi rich in protein and fibre. This study investigated the protein bioaccessibility from the fungal cells by colourimetric assays in different mycoprotein formulations, following extraction methods and in vitro gastrointestinal digestion. The methods effects were further analysed by static laser light scattering, SDS-PAGE and optical-fluorescence microscopy. The extraction methods released a comparable proportion of protein (30 wt%) independent of sample concentration (10 wt% and 25 wt%), whereas the simulated digestions endpoints released a higher proportion of protein from the less concentrated (46 wt%). Furthermore, mechanical/physical processing had only a minor impact. Intestinal proteases promoted the most efficient protein release but without causing any apparent damage to the cell walls when viewed by microscopy. This suggested that the enzymes can diffuse through the cell walls, due to its porosity/permeability, and are the main factors responsible for the hydrolysis and bioaccessibility of protein from mycoprotein.